A CASE STUDY ON THE QUALITY CONTROL OF POULTRY FEED INGREDIENTS IN INDIA - M. Udhayachandran; P. Vasanthakumar; S. Senthilkumar; D. Chandrasekaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to assess the quality control practices of both physical and chemical methods of evaluation adopted by feed mills in India while procuring the feed ingredients for preparing poultry feeds. Based on physical methods of evaluation of different feed ingredients, 6.4 % of lots were found to be inferior quality out of 2606 lots tested. The results indicated that the moisture content of grains procured during the period from October to December months was high whereas it was low from April to July. The protein content of soybean meal varied from 45.5 to 47.5% while its solubility varied from 72.1 to 83.2%. The rejection of raw material consignments was 7.85 %. The major reasons for rejection included high moisture, low protein, high level of sand & silica, adulteration / contamination with foreign materials. the findings of this study emphasis ther sgnificance of strict quality control measures to be adopted to ensure feed and food safety.